Chemopreventive effects of aloin against 1, 2-dimethylhydrazine-induced preneoplastic lesions in the colon of Wistar rats. (February 2014) - Hamiza, OO; Rehman, MU; Khan, R; Tahir, M; Khan, AQ; Lateef, A; Sultana, S
Chemoprevention opens new window in the prevention of all types of cancers including colon cancer. Aloin, an anthracycline in plant pigment, can be utilized as a protective agent in cancer induction. In the present study, we have evaluated the chemopreventive efficacy of aloin against 1, 2-dimethylhydrazine (DMH)-induced preneoplastic lesions in the colon of Wistar rats. DMH-induced aberrant crypt foci (ACF) and mucin-depleted foci (MDF) have been used as biomarkers of colon cancer. Efficacy of aloin against the colon toxicity was evaluated in terms of biochemical estimation of antioxidant enzyme activities, lipid peroxidation, ACF, MDF, histopathological changes, and expression levels of molecular markers of inflammation and tumor promotion. Aloin pretreatment ameliorates the damaging effects induced by DMH through a protective mechanism that involved reduction in increased oxidative stress enzymes ( p < 0.001), ACF, MDF, cyclooxygenase-2, inducible nitric oxide synthase, interleukin-6, proliferating cell nuclear antigen protein expression, and tumor necrosis factor-α ( p < 0.001) release. From the results, it could be concluded that aloin clearly protects against chemically induced colon toxicity and acts reasonably by inducing antioxidant level, anti-inflammatory and antiproliferative markers.